Capabilities and limitations of antibacterial and complex surgical treatment of inflammation-purulent limb lesion - Podpryatov, S. E.; Podpriiatov, S. S.; Korchak, V. P.; Simonova, Z. E.; Korbut, O. M.; Mazurok, L. M.; Satsyuk, I. V. (Modern medical technology, 2019)
Purpose of the study. The effectiveness of limb inflammation-purulent lesions (LIPL) treatment on the base of own experience was estimate. Material and methods. 190 patients were treated for LIPL, including: 1. Acute LIPL – 142 cases, namely: acute complication of diabetes mellitus (phlegmon, arthrosteopathy, tissue necrosis) was found in 119, acute thrombophlebitis against the background of post-thrombophlebitis syndrome 5, lymphangitis against the background of a chronic limb wound in 5, erysipelas in 4, inflammation after manicure/pedicure at 4, scratching a cat at 3, an injection of fish bone at 3, a bite of a parasite in 2 and a bite of a dog in 2 patients. 2. Chronic LIPL was observed in 48 patients who were followed up for 4 months to 13 years. The cause of repeated visits was the formation of a chronic wound/ulcer of the foot or lower leg (35 cases), the re-occurrence of acute inflammation – 13 cases. The background disease was diabetes mellitus in 18 post-thrombophlebitis syndrome complicated by lymphostasis in 17, cancer in 7, systemic collagenosis in 4, and HIV infection in 2 patients. Results and discussion. Complicated wound healing occurs in 39,5% cases of surgeries on acute inflammation and in 37% cases in chronic. Among 104 patients with foot surgery antibiotic treatment was ineffective in 48,1%, high amputation incidence estimates 3,8%. After primary high amputation complicated wound healing estimates 21,7%. By combination of aimed and prolonged antibacterial treatment and full-fledged fasciotomy it was possible to ceased anaerobic non gas producing infection and hand compartment-syndrome. Conclusions. 1. In the case of non-effective antibacterial treatment of the LIPL requires reassessment of the pathogen and the appointment of an appropriate antibiotic, while determining the need for surgical intervention. 2. Dangerous to patient’s life are anaerobic non gas producing infection, which demands instant clindamycin treatment, and sepsis, which demands clindamycin or/and carbapenem treatment. In-time surgery, fasciotomy or limb amputation in the case of such infections needed beside of this. 3. Slow wound cleansing and granulations formation, which lead to prolonged infection and its antibiotic resistance supposed to patient extra examination for revealing concomitant disease and it stabilization.